A longitudinal study on α‐synuclein in plasma neuronal exosomes as a biomarker for Parkinson's disease development and progression. (13th April 2020) - Niu, M.; Li, Y.; Li, G.; Zhou, L.; Luo, N.; Yao, M.; Kang, W.; Liu, J.
Abstract : Background and purpose: The identification of reliable diagnostic and prognostic biomarkers for Parkinson's disease (PD) is urgently needed. Here, we explored the potential use of α‐synuclein (α‐syn) in plasma neuronal exosomes as a biomarker for early PD diagnosis and disease progression. Methods: This study included both cross‐sectional and longitudinal designs. The subjects included 36 patients with early‐stage PD, 17 patients with advanced PD, 20 patients with idiopathic rapid eye movement sleep behavior disorder and 21 healthy controls (HCs). α‐syn levels were measured by electrochemiluminescence immunoassay. A subgroup of patients with early‐stage PD ( n = 18) participated in a follow‐up examination with repeated blood collection and clinical assessments after an average of 22 months. Results: The α‐syn levels in plasma neuronal exosomes were significantly higher in patients with early‐stage PD compared with HCs ( P = 0.007). Differences in α‐syn levels between patients with idiopathic rapid eye movement sleep behavior disorder and HCs did not reach statistical significance ( P = 0.08). In addition, Spearman correlation analysis revealed that neuronal exosomal α‐syn concentrations were correlated with Movement Disorders Society Unified Parkinson's Disease Rating Scale III/(I + II + III) scores, Non‐Motor Symptom Questionnaire scores and Sniffin' Sticks 16‐item test scores of patients with PD ( P < 0.05). After a mean follow‐up of 22 months in patients with early‐stage PD, a Cox regression analysis adjusted for age and gender showed that longitudinally increased α‐syn rather than baseline α‐syn levels were associated with higher risk for motor symptom progression in PD ( P = 0.039). Conclusions: Our results suggested that α‐syn in plasma neuronal exosomes may serve as a biomarker to aid early diagnosis of PD and also as a prognostic marker for PD progression.